Building effective and efficient local government under the spirit of the 2013 Constitution - Dam, Bich Hien (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
The research highlights the significant progress made in decentralization and local autonomy, as guided by the directives of the XIII National Party Congress and the provisions of the 2013 Constitution. The author emphasizes the need for tailored approaches to local government organization, taking into account the diverse characteristics of rural, urban, island, and special administrative-economic units. Pilot programs in major cities like Hanoi, Ho Chi Minh City, and Da Nang exemplify efforts to streamline operations and maximize efficiency in urban settings. However, challenges remain, particularly in fully realizing the distinctiveness of governance and ensuring effective oversight mechanisms. The manuscript concludes by advocating for continued research, legislative adjustments, and administrative reforms to optimize local governance structures and processes. Ultimately, the pursuit of robust and responsive local governance is vital for advancing socio-economic development of Vietnam.